Social network in palliative care: an integrative review of literature - da Costa dos Reis, Cristine Gabrielle (2020)
This work aims to analyze the characteristics of the functions of members of social networks configured around relatives of patients in palliative care. Articles from the past decade were selected from PsycINFO, Web of Science and Scopus. After considering specific descriptors and the study objective, 30 articles were selected. The results showed: a) predominantly qualitative research, b) ambivalent perceptions of caregivers in relation to care offered by institutional support and family networks, c) presence of feelings of exhaustion, gratification, anxiety and depression, during the care process. Further research on aboutpalliative care is necessary in Brazil and other Latin American countries.